The Impact of Self-Control, Self-Esteem and Peer Environment on Online Shopping Consumptive Behavior (Universitas Negeri Semarang, 2019)
Consumptive behavior has been extensively explored by scholars in the traditional consumption environment. However, research on the concept has been somewhat limited in the context of online shopping, particularly the specific types of stimuli among university students. The purpose of this study is to analyze empirically the impact of self-control, self-esteem and peer environment on the online shopping consumptive behaviors. A self-administered questionnaire was developed from the literature was administered to 197 students of Economics Education of Universitas Negeri Semarang. Multiple regression analysis was used to validate the measures developed and test the hypothesized model. The results showed that there is a positive relationship between self-control, self-esteem and peer environment on the online shopping consumptive behaviors simultaneously or partially.